Analisis Pengaruh Faktor Eksternal Dan Internal Pelanggan Dalam Pengambilan Keputusan Pembelian Surat Kabar Harian Borneo Tribune - Dedi Haryanto; Ria Rusmayanti (JURNAL MANAJEMEN MOTIVASI, 2013)
The purpose of this study was to determine the influence of external factors and internal when making a decision to buy Borneo Tribune Daily newspaper. The author uses descriptive methods f and using 100 respondents were using purposive sampling. External variable is an indicator for culture, sub-culture,social class, reference groups / reference and families. Indicators for the internal variables are motivation, perception, learning, and beliefs and attitudes. While the indicator for the decision variables measured through 5 stages of buying decision process konsume purchase. The analytical tool used is multiple linear regression. The results of the study revealed that the external and internal factors significant and positive influence in the purchase decision Borneo Tribune Daily News of 0.581 and 0.400. Based on this value it can be concluded that external factors have a greater influence than internal factors. simultaneous correlation coefficient indicates a strong relationship category. value of F at 145.661> 3.09 so the value Ftable simultaneously (synchronously) does not have significant influence in the purchase decision Borneo Daily News Tribune was denied. t value> of ttable, so the null hypothesis that external factors and internal states partially customers do not have a significant influence in the purchase decision Borneo Daily News Tribune was denied.Keywords: Faktor internal, faktor eksternal, pengambilan keputusan pembelian, Borneo Tribun.